2013
DOI: 10.1186/1471-2105-14-352
|View full text |Cite
|
Sign up to set email alerts
|

Status quo of annotation of human disease variants

Abstract: BackgroundThe ever on-going technical developments in Next Generation Sequencing have led to an increase in detected disease related mutations. Many bioinformatics approaches exist to analyse these variants, and of those the methods that use 3D structure information generally outperform those that do not use this information. 3D structure information today is available for about twenty percent of the human exome, and homology modelling can double that fraction. This percentage is rapidly increasing so that we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…44 The impact of a surface change, however, depends entirely on the spatial context and is therefore less likely to result in misfolding and subsequent protein degradation. 45 Consequently, de novo disease-causing missense mutations preventing proper folding cause protein degradation, and thus indirectly lead to HI, similar to protein truncating mutations in such genes. To test the hypothesis that our clustered de novo missense mutations do not generally result in HI due to protein misfolding, we modeled mutations onto the 3D protein structure using YASARA & WHAT IF Twinset.…”
mentioning
confidence: 99%
“…44 The impact of a surface change, however, depends entirely on the spatial context and is therefore less likely to result in misfolding and subsequent protein degradation. 45 Consequently, de novo disease-causing missense mutations preventing proper folding cause protein degradation, and thus indirectly lead to HI, similar to protein truncating mutations in such genes. To test the hypothesis that our clustered de novo missense mutations do not generally result in HI due to protein misfolding, we modeled mutations onto the 3D protein structure using YASARA & WHAT IF Twinset.…”
mentioning
confidence: 99%
“…However, these tools have moderate sensitivity and low specificity -one study found that 31-32 % of pathogenic variants were predicted to be benign, while 84-87 % of benign variants were predicted to be pathogenic (Flanagan et al 2010;Dorfman et al 2010). More accurate assessments may be gained by considering each variant in the context of the three-dimensional structure of the protein (Venselaar et al 2013;Preeprem and Gibson 2014).…”
Section: Interpreting the Relevance Of Genetic Variation To Phenotypimentioning
confidence: 99%